Design and Analysis of Offshore Wind Turbines: Problem Formulation and Optimization Techniques - Ghaemifard, Saeedeh; Ghannadiasl, Amin (Journal of marine science and application, 2024)
Researchers often explore metaheuristic algorithms for their studies. These algorithms possess unique features for solving optimization problems and are usually developed on the basis of real-world natural phenomena or animal and insect behavior. Numerous fields have benefited from metaheuristic algorithms for solving real-world optimization problems. As a renewable energy source, offshore wind energy is a rapidly developing subject of research, attracting considerable interest worldwide. However, designing offshore wind turbine systems can be challenging because of the large space of design parameters and different environmental conditions, and the optimization of offshore wind turbines can be extremely expensive. Nevertheless, advanced optimization methods can help to overcome these challenges. This study explores the use of metaheuristic algorithms in optimizing the design of wind turbines, including wind farm layout and wind turbine blades. Given that offshore wind energy relies more heavily on subsidies than fossil fuel-based energy sources, lowering the costs for future projects, particularly by developing new technologies and optimizing existing methods, is crucial.